Profile Centric Community Awareness and Engagement for Adolescent Girls : An Empirical Study on Early Marriage in India - Hasti, Charru; Arora, Sonal; Mehndiratta, Amit; Sagar, Mahim; Chaudhry, Harish (Indian Journal of Marketing, 2021)
Early marriage is a pernicious practice traditionally observed even today in several countries, with a fifth of the global female population getting married by 18 years of age. The custom has far-reaching adverse effects on the girls’ physical, mental, and socioeconomic welfare and their future progeny. Therefore, it is critical to disseminate the right messages to the communities of girl children to deter them from letting their daughters marry early. A study was carried out in 2019 that involved the design, execution, and evaluation of a volunteer-driven technology-enabled communication intervention to emphasize the importance of education in securing a girl’s future and to discourage girl child marriage. Seven hundred and eight-six residents of the sub-district of Todaraisingh in Tonk, Rajasthan, participated in the study. A strong positive cognizance of the personalized communication was empirically confirmed. Furthermore, a high influence of cognitive response and sympathy towards the communication was found on the evaluative judgment of the participants that strongly influenced the intention to spread positive word of mouth and behavioral intention.